2011
DOI: 10.1007/s10815-011-9674-x
|View full text |Cite
|
Sign up to set email alerts
|

Maturation outcomes are improved following Cryoleaf vitrification of immature human oocytes when compared to choline-based slow-freezing

Abstract: Purpose The cryopreservation of immature oocytes permits oocyte banking for patients at risk of losing their fertility. However, the optimum protocol for such fertility preservation remains uncertain. Methods The present study investigated the survival, maturation, cytoskeletal and chromosome organization of sibling immature oocytes leftover from controlled ovarian stimulation cycles, that were either slow-frozen (with choline-substitution) or vitrified. A comparison group included oocytes that were never cryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 60 publications
(78 reference statements)
0
27
0
2
Order By: Relevance
“…The debate on how vitrification procedures affect the microfilament network of the immature or mature oocytes has been reported in several studies [8,13,[17][18][19][20][21][38][39][40]. Consequences of vitrification/warming on the actin cytoskeleton depended on the CPAs used, the oocyte maturation stage and varied between species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The debate on how vitrification procedures affect the microfilament network of the immature or mature oocytes has been reported in several studies [8,13,[17][18][19][20][21][38][39][40]. Consequences of vitrification/warming on the actin cytoskeleton depended on the CPAs used, the oocyte maturation stage and varied between species.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the exposure to cryoprotectants and the cold temperatures may lead to the disruption of microtubules and the change of the meiotic spindle morphology of mature oocytes [11][12][13][14][15][16]. Few reports focus on modifications caused by vitrification on the actin cytoskeleton [13,[17][18][19][20][21]. Actin is a major component of the cytoskeleton of the oocyte and it is present as the fibrous polymer, F-actin, in dynamic equilibrium with monomeric globular actin (G-actin).…”
Section: Introductionmentioning
confidence: 99%
“…Unless noted otherwise, all studies discussed herein are in human. Table 2 summarizes the ranges of values obtained from a total of 23 studies that cryopreserved human oocytes at the GV stage, 14 and 12 of which used slow-freezing or vitrification protocols, respectively (Mandelbaum et al, 1988;Toth et al, 1994a;Toth et al, 1994b;Baka et al, 1995;Son et al, 1996;Park et al, 1997;Chung et al, 2000;Goud et al, 2000;Wu et al, 2001;Boiso et al, 2002;Chen et al, 2004;Fuchinoue et al, 2004;Isachenko et al, 2006;Cao et al, 2009;Fasano et al, 2010;Al-Khtib et al, 2011;Combelles et al, 2011;Criado et al, 2011;Liu et al, 2011;Versieren et al, 2011;Zhang et al, 2011;Fasano et al, 2012;Wang et al, 2012). Seventy percent (16/23) of studies evaluated the in vitro developmental competence of cryopreserved GV oocytes based on fertilization, cleavage, and in some instances even blastocyst formation.…”
Section: Advantages and Drawbacks Of Cryopreserving Immature Oocytes mentioning
confidence: 99%
“…It is only with survival rates that there appears to be an overall improvement over time, particularly when comparing data from the 1990's to studies reported in the last ten years with slow-freezing. When it comes to the evaluation of spindles following IVM of cryopreserved GV oocytes, 1 to 35% normal spindles were reported out of the total number of starting oocytes (Baka et al, 1995;Boiso et al, 2002;Combelles et al, 2011;Wang et al, 2012). Four of the studies reported 1%, 5%, 9%, and 35% normal spindles with slow-freezing of GV oocytes, when compared to 26% with vitrification (Combelles et al, 2011).…”
Section: Advantages and Drawbacks Of Cryopreserving Immature Oocytes mentioning
confidence: 99%
See 1 more Smart Citation